2016
DOI: 10.1002/art.39539
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Influence of HLA–DRB1 Susceptibility Alleles on the Clinical Subphenotypes of Systemic Lupus Erythematosus in Koreans

Abstract: Objective. To investigate the association between HLA-DRB1 alleles and systemic lupus erythematosus (SLE) susceptibility and features of SLE, such as clinical manifestations and autoantibody profiles, in a Korean population.Methods. We tested the genetic associations between HLA-DRB1 alleles and SLE susceptibility and clinical subphenotypes in 1,089 patients with SLE and 2,161 control subjects, including a discovery set (475 patients and 1,119 controls) and a replication set (614 patients and 1,042 controls). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
6
15
0
Order By: Relevance
“…Moreover, the most protective, susceptible alleles were identical in both methods, illustrating the usefulness of the DISH method in looking for the most significant alleles in HLA fine-mapping studies. The observed associations of HLA-DRB1 alleles with RA or SLE in DISH-based and HMM-based approaches were supported by previous studies 15,16 that tested for the association for sequenced HLA-DRB1 alleles.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the most protective, susceptible alleles were identical in both methods, illustrating the usefulness of the DISH method in looking for the most significant alleles in HLA fine-mapping studies. The observed associations of HLA-DRB1 alleles with RA or SLE in DISH-based and HMM-based approaches were supported by previous studies 15,16 that tested for the association for sequenced HLA-DRB1 alleles.…”
Section: Discussionsupporting
confidence: 76%
“…To date, the HLA-DRb1*03 and DRb1*15 alleles have consistently been reported to be associated with SLE. Previous studies have shown that HLA-DRb1*15 is associated with SLE in Japanese, Brazilian, Hungarian, Taiwanese and Korean populations, 24,28,29,32,45,46 whereas the HLA-DRB1*03 allele was associated with Hungarian, Taiwanese, Egyptian, Latin American and UK-European Caucasian individuals. 25,28,29,31,32 The association of the HLA-DRb1*04 allele with SLE was reported in Swedish, European Caucasian and Egyptian populations.…”
Section: Discussionmentioning
confidence: 94%
“…Some loci have been associated to increase the risk of SLE; for example, complement components C1q and C4, major histocompatibility complex (especially the human leucocyte antigen, class II), T cell receptor and many cytokines (IL-6, IL-27, IL-12, IL-23) [5,6]. At the same time, some are typically related to other autoimmune diseases as diabetes or rheumatoid arthritis (RA) (PTPN22 and STAT4) [7].…”
Section: Introductionmentioning
confidence: 99%